Linguistic features in SMS apologies by Malay native speakers - Ernisa, Marzuki (Universiti Kebangsaan Malaysia, 2013)
The emergence of communication channels such as the Short Message Service (SMS) gives rise to a different variety of language use, also known as textism. Textism is viewed as a hybrid form of communication as it merges the forms of both spoken and written language. Textism features are arguably part of the pragmalinguistic domain, which looks at the selection of strategies which can be applied in conveying illocutions. This study sheds some light on the pragmalinguistic conventions reflected in apologies conducted via SMS or text messages. Twenty six Malay native speakers responded to Written Discourse Completion Tasks (WDCT) via SMS. The WDCTs were categorised into two levels of offence which required the participants to apologise by texting their apologies. Data were categorised and coded based on adapted versions of coding schemes by Supyan (2006) and Crystal (2008). The results indicated that there were three significant variations in the SMS linguistic features used by the Malay Native Speakers (Malay NS) when apologising via SMS in their first language, Malay, and their second language, English. Differences were also identified when the apologies were sent because of more serious transgressions compared to when they were sent because of less serious offences. The findings suggests that the first language contribute to these differences in the selection of textual features when the participants texted their apologies.